Mosquitos aedes aegypti são vetores potenciais de leishmaniose? - Relato de caso - Coelho, Willian Marinho Dourado [UNESP]; Bresciani, Katia Denise Saraiva [UNESP]; Coêlho, Juliana de Carvalho Apolinário; dos Anjos, Luciano Alves [UNESP]; Buzetti, Wilma Aparecida Starke [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2017)
In Brazil dipters of the Lutzomyia genus are the main vectors of leishmaniasis for humans and animals. However, other hematophagous insects such as ticks, fleas, and horse flies may also be considered potential vectors of this protozoon. This paper, regarding an endemic area for visceral leishmaniasis, is the the first description of the Leishmania spp. presence in Aedes aegypti mosquitoes. Two A. aegypti mosquitoes were captured: one of them was feeding on a polysymptomatic dog with leishmaniasis, confirmed by parasitic demonstration and positive PCR for Leishmania spp., and the other was collected in the environment where the dog was isolated. The mosquito engorged with dog’s blood was crushed between two microscopic slides and the other one was processed by the polymerase chain reaction assay (PCR) searching for the presence of Leishmania spp. DNA. Amastigote forms of Leishmania sp, were observed in the smear prepared from one mosquito by microscopic examination, as well as other protozoa’s flagellated forms. In the other insect it was observed Leishmania DNA amplification. This observation reinforces the role of dogs as sources of infection of Leishmania spp. even to other potential vector species.
Are aedes aegypti mosquitoes potential vectors for leishmaniasis? - Case report
Keywords: Amastigote; Canine; Parasite; Vectors; Zoonosis